(untitled) (Revista Inclusiones, 2019)
The authors attempt to conduct an in-depth analysis of the problems associated with cultural heritage as a spiritual, cultural, and economic capital of irreplaceable values. It is established that the physical condition of more than half of the state-protected monuments of history and culture of Russia continues to deteriorate, and currently is characterized as unsatisfactory. Monuments of nature, history, and culture of Russia make a significant contribution to the cultural and natural heritage of the world ensuring the sustainable development of the country and human civilization in general that predetermines the highest responsibility of the peoples of Russia and the state for the preservation of their heritage and its communication to subsequent generations.